RESERVOIR QUALITY ANALYSIS OF ZONES I, G, F, AND E IN NAYA FIELD, KUTAI BASIN, EAST KALIMANTAN - ADLIANI KEMALA (NIM : 12011036), FIDHIA
Naya Field is one of oil fields located in Kutai Basin, East Kalimantan. This field consists of seven main zones with research area located in one of intervals within four main zones which are I, G, F, and E that belong to Balikpapan Group. Within those four intervals, production rate is identified as not yet optimum. Thus, geological condition from reservoir rocks acting in those intervals needs to be redefined by determining sedimentation facies, depositional environment, map of reservoir distribution from stratigraphic interval represented by core data from four wells and 41 well logs, as well as map of reservoir quality distribution represented by volume of shale and effective porosity to give references for next development stage. Core analysis shows that lithofacies in those four zones are: ten sandstone lithofacies which are Spa, Scc, St, Sp, Stc, Sfp, Scr, Swb, Sf, and Ssc; six claystone-siltstone lithofacies which are M, Ml, Mlb, Mb, Flp, and Fb; and two coal lithofacies which are C and Cs. From core and electrofacies analysis, correlation, and mapping of sandstone interval distribution, research area is located in delta environment. The sedimentation facies developed here are distributary channel, distributary mouth bar, interdistributary-plain, delta front mud, and prodelta mud with depositional direction SW-NE. Petrophysical analysis in distributary channel of reservoir I, G, F, and E shows mean effective porosity value of 0,16; 0,16; 0,17; and 0,17 respectively, while volume of shale value are 0,16; 0,19; 0,18; and 0,2 respectively. In addition, petrophysical analysis in distributary mouth bar of reservoir I, F, and E shows effective porosity value of 0,07; 0,08; and 0,08 respectively, while volume of shale value are 0,24; 0,28; and 0,29 respectively. Hence, reservoir quality distribution analysis from every research zone indicates that sandstones deposited in distributary channel has relatively better reservoir quality than those deposited in distributary mouth bar.